A novel concept for improved thermal management of the planar SOFC - Periasamy, Vijay; Hosseini, Shahin; Tade, Moses (Institute of Chemical Engineers (IchemE), Elsevier B.V., 2013)
A new design for the solid oxide fuel cell (SOFC) planar stack is proposed to minimise the thermal gradients in the cell. This design involves including a secondary air channel with flow in the counter direction to the cathodic air channel. The effectiveness of the new design is tested by means of a tank in series reactor (TSR) model of the SOFC. It is found that the new design is capable of reducing the steady state temperature difference across the cell to less than 2 K over a range of voltages, while satisfying the requirements on fuel utilisation (FU) and cell average temperature. This is achieved by manipulating the primary air channel inlet flow rate and the secondary air channel inlet temperature.More modelling and experimental studies are required to further investigate the proposed design.